Capacity Utilization in the Fish Processing Plants in Kerala - G.R., Unnithan; A.K., Kesavan Nair; H., Krishna Iyer; V, Annamalai (Fishery Technology, 2025)
The production and capacity utilization in the fish processing plants in Kerala was estimated using a stratified random sampling procedure. The capacity utilization for the year 1996 was estimated to be 15% based on 365 working days with three shifts per day. The seasonal production and capacity utilization indicate that trawl ban adversely affected the processing industry during June, July months (about 10.6% utilization) whereas the utilization increased substantially during post ban period (about 25%). This increase was observed to be mainly due to the increased production of squids, cuttlefish and other diversified products. The main reason for the low capacity utilization was that the availability of raw material was not commensurate with existing installed capacity in the fish processing sector in the State.